Comparative Advantage and Economic Geography: Estimating the Location of Production in the EU. - Midelfart, K; Overman, H; Venables, A (CEPR, 2000)
We develop and econometrically estimate a model of the location of industries across countries. The model combines factor endowments and geographical considerations, and shows how industry and country characteristics interact to determine the location of production. We estimate the model on sectoral data for EU countries over the period 1980-97, and find that endowments of skilled and scientific labour are important determinants of industrial structure, as also are forward and backward linkages to industry.